Драматизм лірики Лесі Українки: жанровий аспект - Левчук, Юлія Олександрівна; Levchuk, Yuliia O. (Таврійський національний університет імені В. І. Вернадського, 2014)
Стаття присвячена проблемі театру і театралізації в драматичній творчості Лесі Українки. Завдання дослідження – виокремити моделі театру, що функціонують в драматичних творах Лесі Українки. Автор аналізує чотири типи репрезентації топосу театру в творчості Лесі Українки: зображення богемного антуражу («Блакитна троянда»); характеристика публічних виступів, побудованих за аналогією з театральним лицедійством («Кассандра», «Адвокат Мартіан»); включення театралізованого дійства як важливого чинника сюжетобудування («Оргія», «Адвокат Мартіан»); створення концептуального портрету глядача («Руфін і Прісцілла»). Доведено, що в драматургії Лесі Українки переважає імітація театрального дійства, яке створює додатковий вимір текстів, ускладнюючи їх конституцію. Видовища на площах, оргіях, у цирку, суді, що мають місце в творах Лесі Українки, є самодостатніми естетичними цінностями, відповідними креативним законам театру.

The paper considers the problem of genre structure of lyrical work in terms of drama. Material studies provided two versions of sonnet «Fa» (1890) from the series «Seven String» and poetry «Sonnet» (1890) and «I look at the death of nature» (1890). Methodological basis of scientific research is the concept of cognitive models of J. Lakoff and the theory of genre patterns as the minimum differential elements of the genre. We show also the psychological background to the formation of dramatic thinking. In terms of psychology, thinking - is the highest form of mind mapping and dramatic results from the interaction of thought (mind) and feelings. Attention is focused on creative thinking, originality reflected by a problem , semantic flexibility that allows you to see the object from a new angle, shape adaptive flexibility, which make it possible to change the object with the development needs of its knowledge, semantic spontaneous flexibility as the production of different ideas for uncertain situations. The author draws attention to one of the main features of the sonnet as a genre, namely, dramatic theory, that is a combination of thesis, antithesis and its synthesis. However, the problem is posed so, that the figure appears as a dramatic thought of poet in the sonnet, regardless of genre and style features. Separately, referred to the two versions of the sonnet «Fa», which differ significantly from each other and demonstrate against rational and irrational principles in the face of the Lesya Ukrainka. It turned out that the first version is much emotional and therefore much more deviates from the canonical sonnet. Instead, the second edition reflects the tradition declaratively symbolist poetics. In this aspect, the author uses the theory of I. Franko on «lower» and «upper» consciousness , pointing out that the first version of the sonnet is the result of the «bottom» of consciousness without control of «top» consciousness, that this verse is continuous subconscious impulse feelings.In this paper develops the theory of gestalt structure (J. Lakoff) in terms of which the mind is seen as an instant flash of thought, and , accordingly, the genre as a spontaneous arrangement of genre patterns. According to the author, gestalt terms of genre science be called an integrated feature, that is genre, consisting of a combination of various genres (often unconnected to each other), which in turn interact (with the will of the author ), form a genre is not modified, and a new genre built by the copyright laws of individual thinking. Subsequent analyzes the works of «Sonnet» and «I look at the death of nature» between which revealed a close relationship to the level of the genre. Both pieces are sonnets , but the first of them – a thesis for the second, so it appears that Lesya Ukrainka expanded beyond the genre sonnet, creating a three-dimensional picture of the lyrical experiences with integrated genre. In theory of J. Lakoff, genres can be based on two structures: the structure of the building blocks and structure of gestalt. The article argues that this theory is quite close to the concept of F. Nietzsche about Dionysius and Apollo types of writing. That feature of this view can be built in two ways: as a deliberate, consciously designed by the creators of genre features or as spontaneous momentary impulse of thought, in which the author unconsciously composes genre based of work.As a result, we found out that the dramatization of creative thinking of Lesya Ukrainka, caused by internal opposition of mind and heart, and the proper to writer rational and irrational types of writing, greatly influence the formation of the sonnet genre in particular and in general any lyric genre. The writer often creates dialogical pieces that lyrical hero speaks to an unknown destination, or whether the recipient – abstract occurrence (for example, imagination).
Dramatization of the poetry of Lesya Ukrainka: genre
Keywords: драматизм; dramatization; лірика; poetry; сонет; sonnet; жанр; genre; патерн; pattern